2016
DOI: 10.1111/ffe.12478
|View full text |Cite
|
Sign up to set email alerts
|

Non‐local line method for notched elements with use of effective length calculated in an elasto‐plastic condition

Abstract: The paper presents a non‐local line method used to the fatigue life calculation of notched elements. The presented method is based on the concept of an effective length which determines the size of the equivalent fatigue zone. Effective values of normal stress calculated in the critical plane with a weight function were applied when determining the equivalent fatigue zone. Simulation studies were performed for two types of steel and two types of loading. Five different series of tests and simulations were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The critical distance is often determined by the effective crack length l 0 introduced by El Haddad or an empirically derived value. Successful applications were reported [37,38] on the homogeneous models. It is expected that the critical zone has some connections with the microstructure.…”
Section: Non-local Methodsmentioning
confidence: 99%
“…The critical distance is often determined by the effective crack length l 0 introduced by El Haddad or an empirically derived value. Successful applications were reported [37,38] on the homogeneous models. It is expected that the critical zone has some connections with the microstructure.…”
Section: Non-local Methodsmentioning
confidence: 99%
“…However, there are publications showing that notches are improving the LCF fatigue lives of specimens, e.g., for conventionally cast or even directionally solidified Ni-base superalloys 13,41,42 and steels. 13,31,[43][44][45] Interestingly, Haibach and Matschke et al 31 observed improvements in LCF lives, but HCF strength reductions at notched steel specimens. Furthermore, Eriksson et al 41,46 noted that the LCF notch support at high loads changed to notch weakening at lower load amplitudes for the Nibase alloy IN-718.…”
Section: Introductionmentioning
confidence: 98%
“…Sometimes, this was not even indicated, or no comparison with a smooth specimen Wöhler curve was provided, which makes it hard to judge whether a notch improves or decreases the fatigue life. However, there are publications showing that notches are improving the LCF fatigue lives of specimens, e.g., for conventionally cast or even directionally solidified Ni‐base superalloys and steels . Interestingly, Haibach and Matschke et al observed improvements in LCF lives, but HCF strength reductions at notched steel specimens.…”
Section: Introductionmentioning
confidence: 99%